Interrelation Between Tourism Destination Financial Management and Tourist Experiences: Qualitative Approach to Literature - Damiasih, D. (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research investigates the intricate interplay between tourism destination financial management and tourist experiences. The study aims to address existing gaps in literature by exploring how financial decisions made by destination authorities influence the quality, diversity, and authenticity of tourist experiences. Employing a qualitative thematic analysis approach, the research synthesizes insights from contemporary studies to provide a comprehensive understanding of this complex relationship. Methodological challenges, including data availability and measurement validity, are acknowledged, and the study seeks to overcome these obstacles through interdisciplinary collaboration and innovative research methodologies. The findings highlight the pivotal role of destination financial management in shaping tourist perceptions, behaviors, and satisfaction levels. Strategic investments in infrastructure, amenities, and destination branding initiatives emerge as key determinants of destination attractiveness and visitor engagement. Additionally, the study underscores the importance of sustainability-oriented financial management strategies in fostering destination resilience and enhancing tourist experiences. Collaborative partnerships involving tourists, destination authorities, industry practitioners, and local communities are essential for developing holistic strategies that balance economic growth with environmental conservation and socio-cultural preservation. The research contributes to evidence-based policy formulation and managerial decision-making in the tourism industry, ultimately enhancing the sustainability and competitiveness of tourism destinations worldwide.